2 - Musical Hybridity in Flux: Representing Race, Colonial Policy, and Modernity in French North Africa, 1860s-1930s - Jann Pasler (Afrika Zamani, 2022)
Colonialism posed the challenge of coexistence amid almost insurmountable differences. Music had long been considered an audible representation of these differences, the performance of intelligence, character, and even soul. However, if music offered a way to understand traditions and values of other peoples, the context for this was racial theories - monogenism and polygenism - and racial hierarchies based on stereotypes. Depending on one’s orientation, studying African music was either a step toward an imagined universalism in the language of music or a mode for contemplating racial distinctions, both helping the French reflect on the ideology of Western superiority. At the same time, music was capable of far more. Because, as art, its meaning is never entirely graspable, music seemed neutral, a domain that could be shared. In this sense, some wanted it to assist in the process of assimilation, thereby infusing energy into the colonial process.